102 Impact of weaning strategy on beef cow-calf behavior and activity - Alexander, Molly (J Anim Sci, 2020)
The objective of this study was to investigate the impact of three weaning strategies on cow and calf behavior and activity. Research has shown that weaning imposes stress on both the cow and the calf that can alter behavior, activity, and growth performance. Angus-based cow-calf pairs (n = 147) were randomly assigned to one of three treatment groups, abrupt weaning on d0 (Abrupt, n=50), fence-line contact for 7 days and then relocation of the cow on d7 (Fence, n=50), and late weaning by abrupt separation on d84 (Late, n = 47). Both cow and calf behaviors were observed over 7d prior to weaning and 7d post weaning activity for each treatment group. A single observer recorded activity and vocalizations for each animal twice in morning and evening on observation days. Calf activity was also continuously measured using accelerometers secured to collars worn by five calves per treatment group. Observation and activity data were analyzed using PROC MIXED of SAS. Significance was determined at P < 0.05 and a tendency at 0.05< P ≤0.10. The average activity units per day (AU/d) prior to weaning were similar among treatment groups. On d1 of weaning, Fence calves, who still had a visual contact with their dam, tended to have greater AU/d (P = 0.09) than the Abrupt calves and maintained a higher level of activity through d14 (P < 0.001). Late calves tended to have greater AU/d (P = 0.10) than Abrupt or Fence on d0-1 after their weaning. No difference in vocalizations (P = 0.41) by calves 7d post weaning were observed (1% Abrupt, 0% Fence, and 4% Late). More cows on Fence paced (1%) than Abrupt (0%) or Late (0%) (P < 0.05) in the 7d of fenceline contact. Late cows (2%) vocalized more than Abrupt (1%) or Fence (0%) when their calves were still with them (P < 0.05), but not after (P > 0.05) when no vocalizations were recorded. These results differ from the previous year study; therefore, further investigation of the impact of weaning strategy on cow-calf behavior and activity is warranted.